The Effect of Growth Mindset on Student Academic Resilience: Comparative Studies in Indonesia and Malaysia - Ramadhona, Rossa; Sutrisman, Henny; Padua, Shirley; Sicat, Alvin; Kusumo, Bayu; Simanjuntak, Rossmery (Yayasan Minang Darussalam, 2024)
This study investigates the impact of growth mindset on academic resilience among students in Indonesia and Malaysia. A growth mindset, characterized by the belief that abilities can be developed through dedication and hard work, is hypothesized to enhance students' resilience in facing academic challenges. This comparative study employs a mixed-methods approach, utilizing quantitative surveys and qualitative interviews to gather data from students across various educational institutions in both countries. The findings reveal that students with a pronounced growth mindset demonstrate higher levels of academic resilience, evidenced by their ability to cope with setbacks and maintain motivation during difficult times. Moreover, cultural factors influencing mindset development and resilience strategies are explored, highlighting both similarities and differences between Indonesian and Malaysian students. The study concludes that fostering a growth mindset can significantly enhance academic resilience, suggesting implications for educational practices and interventions aimed at improving student outcomes. Keywords : Growth Mindset, Academic Resilience, Comparative Study, Indonesia, Malaysia, Educational Psychology, Student Outcomes.